Evaluating Thromboprophylaxis Strategies for High-Risk Pregnancy: A Current Perspective - Lucia Stančiaková; Kristína Brisudová; Ingrid Škorňová; Tomáš Bolek; Matej Samoš; Kamil Biringer; Ján Staško; Juraj Sokol (MDPI AG, 2024)
Venous thromboembolism (VTE) represents one of the leading causes of death during pregnancy. The greatest risk for it is the presence of medical or family history of VTE, stillbirth, cesarean section and selected thrombophilia. Appropriate thromboprophylaxis has the potential to decrease the risk of VTE in at-risk pregnant patients by 60-70%. Based on this, the authors reviewed the PubMed, Web of Science and Scopus databases to identify the possibilities of thromboprophylaxis in pregnant patients with a high risk of VTE. Moreover, they summarized its management in specific situations, such as cesarean delivery or neuraxial blockade. Currently, low-molecular-weight heparins (LMWH) are the preferred drugs for anticoagulant thromboprophylaxis in the course of pregnancy and postpartum due to easy administration and a lower rate of adverse events.